THU0417 Whole body distribution and clinical associations of telangiectasia in systemic sclerosis: a cross-sectional study. (12th June 2018) - Jouvray, M.; Launay, D.; Dubucquoi, S.; Sobanski, V.; Podevin, C.; Lambert, M.; Morell-Dubois, S.; Maillard, H.; Hatron, P.-Y.; Hachulla, E.; Giovannelli, J.
Abstract : Background: Telangiectasia (TA), one of the diagnostic criteria for systemic sclerosis (SSc), could be a clinical marker for the severity of vasculopathy, including pulmonary hypertension (PH). Objectives: We designed a cross-sectional study: (i) to describe the whole-body distribution of TA, (ii) to assess the associations between the whole-body number of TA and the characteristics of patients, (iii) to determine whether the number of TA may be useful to discriminate SSc-PH patients. Methods: Patients were included in the National Referral Centre for Rare Systemic And Autoimmune Diseases if they fulfilled the 2013 ACR/EULAR criteria for SSc. They were excluded if they had received laser treatment. The whole-body number and distribution of TA were recorded at inclusion. The associations were studied using univariate, adjusted and multiple linear regressions. Results: 106 patients were enrolled, including 12 with PH. The median (interquartile range) number of TA was 30 (82.7). Their distribution was: 37.2% on the face, 33.2% on the upper limbs including 26.4% on the hands, 28.1% on the trunk including 17.1% for the upper part of the trunk, and 1.5% on the lower limbs. Using multivariate linear regression model, the whole-body telangiectasia number was independently associated with male gender (percentage change (95% CI)=+144.4% (7.5; 455.9), p=0.033), pulmonary hypertension (+162.8% (5.6; 553.8), p=0.038), history of pulmonary embolism (+336.4% (39.0; 1270.1), p=0.012), glomerular filtration rate (−1.6% (-3.2; −0.1) per 1 ml/mn/1.73m 2 increase, p=0.038) and soluble endoglin (+28.2% (1.2; 62.5) per 1 ng/ml increase, p=0.039). The ROC analyses assessing the ability of telangiectasia to discriminate the presence of pulmonary hypertension revealed that the area under the curve was significant for the telangiectasia number on the whole body (0.77 (0.57; 0.88)), on the hands and face (0.81 (0.57; 0.91)) and on the hands (0.77 (0.57; 0.89)). Conclusions: In SSc-patients, TA were predominantly located on the face, hands and the upper part of the trunk. They may reflect the vasculopathy of SSc and could represent a clinical biomarker for vascular disease, particularly for PH, one of the most severe vascular complications of the disease. References: [1] Johnson SR. Curr Rheumatol Rep2015;17(5):32. [2] Mould TL, et al. Asian Pac J Allergy Immunol2000;18(4):195–200. [3] Robert-Thomson, et al. Asian Pac J Allergy Immunol2002. [4] Shah AA, et al. J Rheumatol2010;37(1):98–104. [5] Hurabielle C, et al. Arthritis Care Res2015October. [6] Zhang S, Xu D, Li M, et al. Telangiectasia as a potential clinical marker of microvascular lesions in systemic sclerosis patients from EUSTAR data in China. Clin Exp Rheumatol2015;33(4Suppl 91):S106–110. Disclosure of Interest: None declared